From lamp to lever: toward a peripheral inferentialism and expressivism - Silva, Marcos (Sofia, 2026)
This article proposes a critical reformulation of semantic inferentialism and logical expressivism from a peripheral perspective. It argues that, for groups subjected to regimes of racial, colonial, and gender domination, language should be conceived neither as a mirror of reality nor merely as a lamp that makes explicit norms already operative in language games. Such regimes of domination are analyzed as forms of grammatical violence, understood as the imposition of networks of material inferences that not only fix the meaning of the concepts operative in our language games but also prey upon the grammar of an autochthonous form of life, insofar as they redistribute authority, value, recognition, and exclusion. Concepts such as “race” and “gender” function as conceptual axes with high inferential density that naturalize hierarchies under the appearance of normative neutrality. A distinction is thus drawn between inferential bootstrapping and grammatical levers. The former designates the process of making rules explicit while participating in the practices that confer meaning upon them. Grammatical levers name situated interventions that identify conceptual fulcrums within these inferential networks and, beyond making them explicit, mobilize collective action to shift them. The paper also discusses normative “aquilombamento” as a historical form of collective consolidation of alternative grammars. Examples such as the Quilombo dos Palmares, the activism of Malcolm X, and the Black Panthers are analyzed as struggles for grammatical sovereignty and normative self-determination by minoritized groups within supremacist language games, rather than as demands for mere assimilation, integration, or expansion of civil rights.